Clonidine as an Adjuvant for Caudal Analgesia in Pediatric Patients Undergoing Infraumbilical Surgery: A Case Report - Khalid Walid Ahmad; Tjokorda Gde Agung Senapathi (HM Publisher, 2023)
Background: Caudal block is a popular regional anesthetic procedure used in pediatric patients because it is easy and provides a significant analgesic effect, especially infraumbilical surgeries. Clonidine, an alpha 2 agonist, was previously used for antihypertensives but has recently been found to have analgesic properties, which have been demonstrated in several studies. A number of mechanisms have described how clonidine can exert an adjuvant effect on local anesthetic drugs. Case presentation: A 6-month-old toddler girl with a planned operation posterior sagittal anorectoplasty. The patient underwent a caudal block with a regimen of 0.25% bupivacaine + 8 mcg clonidine in 10 ml of 0.9% NaCl. Postoperative patient care was carried out in the usual ward with the analgesic regimen of paracetamol syrup 80 mg every 6 hours and ibuprofen syrup 80 mg every 8 hours. Conclusion: Clonidine, as an adjuvant for the caudal block, has greater benefits than its side effects in pediatric patients undergoing surgery, especially in areas infraumbilical.